2001
DOI: 10.1179/135100001101536436
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in a progressive neurodegeneration model of Parkinson's disease in the rat

Abstract: This study was undertaken to investigate the nitric oxide synthase (NOS) activity in the striatum following 6-hydroxydopamine (6-OHDA) induced neurodegeneration in rats. Constitutive NOS (cNOS) activity remained unaltered at 3, 7 and 14 days after lesion, while a 43% and 45% decrease was observed at 30 and 50 days, respectively. Inducible NOS (iNOS) activity was detected only on the 3rd day after lesion and not in subsequent days or the control striatum. N(G)-nitro-L-arginine methyl ester (L-NAME) pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 30 publications
1
49
0
2
Order By: Relevance
“…In addition, a potential role for NO in PD has also been given support from studies in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) rodent model in which treatment with the non-selective NOS inhibitor or knockout of the iNOS genes protected DA neurons (Barthwal et al, 2001; M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a potential role for NO in PD has also been given support from studies in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) rodent model in which treatment with the non-selective NOS inhibitor or knockout of the iNOS genes protected DA neurons (Barthwal et al, 2001; M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 98%
“…, and amyloid-b (Ab) (Barthwal et al 2001;Mercer et al 2005;Guan et al 2006a, b;Liu et al 2008), did not show a significant protective effect against 6-OHDA-induced DA neuron loss in zebrafish (Fig. 3).…”
Section: Chemical Analysis Of Aoementioning
confidence: 73%
“…Exposure to 6-OHDA results in the formation of reactive nitrogen species (RNS) and reactive oxygen species (ROS), which can contribute to neuronal cell injury and death . It has been shown that the oxidative damage induced by 6-OHDA can be prevented by antioxidants (Guo et al 2005), as well as by L-NAME, a non-specific NOS inhibitor that has been proved to protect PC12 cells against 6-OHDA-induced cytotoxicity by inhibiting NO production, and to exert significant neuroprotection in an in vivo PD model (Barthwal et al 2001;Gao et al 2003;Wang et al 2011) This study showed that AOE has a protective effect in PC12 cell injury induced by 6-OHDA. Moreover, AOE Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, such data provide grounds for a production of NO by DAergic cells, together with an afferent NO input that could affect DA neurons through diffusion from neighbouring sources. Strikingly, NOS + neuron numbers within the SNc and the BG in general are subject to modification, for example nigral nitrergic neurons increase after intoxication with 1-methyl 4-phenyl 1,2,3,6-tetrahydropyridine (MPTP) [38] and rotenone [39] but decreases after 30 and 50 days from 6-hydroxydopamine (6-OHDA) administration [40].…”
Section: No Distribution In the Bgmentioning
confidence: 99%